Distribution and ecological health risk assessment of dissolved trace metals in surface and bottom seawater of Yantai offshore, China - Liang, Yan; Pan, Dawei; Wang, Chenchen; Lu, Yuxi; Fan, Xia (Frontiers in Marine Science, 2022)
The biogeochemical cycle of trace metals plays an important role in the coastal zone. The distribution, interaction, and biogeochemical behavior of dissolved trace metals in surface and bottom seawater are still unclear. This study analyzed the distribution and performed an ecological health risk assessment of dissolved trace metals (Zn, Cd, Co, Pb and Cr) in surface and bottom seawater in the summer (August) of 2019 and 2020 in the seawater of the Yantai offshore area, China. Zinc (Zn), cadmium (Cd), cobalt (Co), lead (Pb) and chromium (Cr) ranged from 23.76–117.47 μg/L (42.67 μg/L ± 15.15), 0.21–0.51 μg/L (0.30 μg/L ± 0.05), 0.90–2.94 μg/L (1.09 μg/L ± 0.31), 0.13–1.06 μg/L (0.39 μg/L ± 0.17), and 2.00–9.9 μg/L (5.38 μg/L ± 2.99) in the summer of the two years. The average metal (Zn and Co) concentrations were slightly higher than the other Chinese coastal areas, while the major contamination pressures were from Zn and Pb. The largest contaminants were in the following order: Zn > Pb > Cd > Cr > Co. Correlation analysis, principal component analysis and hierarchical cluster were used to determine the potential origins and cause the spatial distribution of the multiple dissolved trace metals. The major sources of the trace metal contamination in study area were identified as external inputs from natural human and atmospheric settling and the natural release of the trace metals in sediments under external disturbances. Riverine inputs, the Lubei coastal current and aquaculture significantly influenced the multi-parameter horizontal distributions of the dissolved trace metals and dissolved organic carbon. Although the growth of phytoplankton was strong in summer, the uptake of Zn, Cd, Co and Pb was negligible compared with the exogenous input. The concentrations of Zn, Cd, Co and Pb were higher in the surface than those in the bottom. Monsoons, tides and wind waves also influence the migration, transformation and distribution of dissolved trace metals and dissolved organic carbon. This study provides important information on the biogeochemical cycle process (migration and conversion) and distribution of dissolved trace metals at different depths in coastal and marine pasture areas.